Grounded Theory sebagai Metode Riset “Realitas Tertambah” di Museum Fatahillah - Leonardo Widya (Jurnal Rekayasa Elektrika, 2013)
Augmented Reality (AR) is part of the science of visual communication design/graphic design through theaddition of images on the real world with virtual information to enhance one’s senses with the help of “smart glasses”with three general characteristics: 1). The combination of real environment with virtual objects, 2). Interactivedisplay, 3). Display in 3D. Qualitative research methods and grounded theory approach in the real environmentin the area of Jakarta Fatahillah museum, discovered a new theory as a basis the idea that Visual PrototypingAugmented Reality technique with image manipulation-image nuanced Kota Tua as Jakarta Icon. The idea ofexploiting foreign tourists enriching way to learn more about Indonesia through social networking in a virtual worldstrategies to increase tourism.